Physico-chemical properties of Jatropha curcas oil during storage - Srivastava S.; Gupta G.N.; Sinha A.; Srivastava V.; Srivastava A. (My University, 2025)
Biodiesel is a renewable alternative fuel for the diesel engine derived from natural sources like Jatropha curcas oil. The present study was to estimate the changes that occur in physico-chemical properties of oils extracted from stored Jatropha seeds in comparison to fresh Jatropha seeds. Physico-chemical properties of Jatropha oil viz. acid value, iodine value, saponification value, UV spectroscopy, cetane value, refractive index, viscosity were estimated. All the values were higher in stored seed oil except iodine value which was lower than fresh seeds. The acid value, saponification value, refractive index and viscosity shows negative effect on the quality of Jatropha oil while decrease in iodine value and increase in cetane value is preferable for better quality bio-diesel. © 2015, Indian Society of Agricultural Biochemists. All rights reserved.